2001
DOI: 10.1080/00221320109597959
|View full text |Cite
|
Sign up to set email alerts
|

The Leftward Cradling Bias and Prosody: An Investigation of Cradling Preferences in the Deaf Community

Abstract: Popular theory on the tendency to cradle an infant to the left side points to the specialization of the right hemisphere for the perception and expression of emotion. J. S. Sieratzki and B. Woll (1996) recently suggested that more emphasis be placed on the auditory modality, specifically focusing on the role of prosodic information. In this study, the direction of the lateral cradling bias in a group of profoundly deaf children, a group of deaf adults, and a control group of adults with no hearing impairment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…An investigation into the relationship of leftward cradling bias and processing of prosody with individuals who are profoundly deaf also revealed interesting results. Turnbull et al [41] observed similar rates of leftward cradling behaviours in profoundly deaf children, deaf adults and a control group of adults with normal hearing. The stimulus used in this study was a doll meant to simulate a new-born.…”
Section: Cradling Bias Of Atypical Populationsmentioning
confidence: 81%
See 1 more Smart Citation
“…An investigation into the relationship of leftward cradling bias and processing of prosody with individuals who are profoundly deaf also revealed interesting results. Turnbull et al [41] observed similar rates of leftward cradling behaviours in profoundly deaf children, deaf adults and a control group of adults with normal hearing. The stimulus used in this study was a doll meant to simulate a new-born.…”
Section: Cradling Bias Of Atypical Populationsmentioning
confidence: 81%
“…The stimulus used in this study was a doll meant to simulate a new-born. Results indicated a strong leftward cradling bias in all groups and, the authors noted, the bias appeared even stronger in individuals who were deaf [41]. The leftward cradling tendency was the subject of an experiment by Fleva and Khan [42] who observed cradling behaviours in typically developing adults on the autism spectrum.…”
Section: Cradling Bias Of Atypical Populationsmentioning
confidence: 98%
“…Salk (1973) reported no association between maternal hand preference and maternal cradling bias, which may have led some to believe that the asymmetries in maternal cradling bias are due to biases related to expression of specific emotional states (Sieratzki and Woll, 1996). Whether this is the case or not is a matter of debate beyond the scope of this paper (Bencie and Sieratzki, 2002;Turnbull et al, 2001).…”
Section: Introductionmentioning
confidence: 93%
“…IN A RECENT ARTICLE in this journal, Turnbull, Rhys-Jones, and Jackson (2001) presented data on the cradling behavior of deaf participants as evidence against the hypothesis that a leftward cradling bias (LWCB) for young infants may be related to a left earhight hemisphere advantage for the perception and processing of prosodic speech (Sieratzki & Woll, 1996). On the basis of their finding that deaf participants show an even stronger LWCB than hearing participants and their assumption that "profoundly deaf people are unable to detect any form of auditory prosody" (p. 179), Turnbull et the perception of prosody by deaf people and the role of speech in the communication between deaf mothers and their young infants that show that the conclusion of Turnbull et al is faulty.…”
Section: Please Scroll Down For Articlementioning
confidence: 97%